2003
DOI: 10.1037/0022-3514.84.1.97
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating autonomy from individualism and independence: A self-determination theory perspective on internalization of cultural orientations and well-being.

Abstract: On the basis of self-determination theory (R. M. Ryan & E. L. Deci, 2000) and cultural descriptions drawn from H. C. Triandis (1995), the authors hypothesized that (a) individuals from different cultures internalize different cultural practices; (b) despite these differences, the relative autonomy of individuals' motivation for those practices predicts well-being in all 4 cultures examined; and (c) horizontal practices are more readily internalized than vertical practices across all samples. Five hundred fifty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

51
721
3
40

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 993 publications
(815 citation statements)
references
References 59 publications
51
721
3
40
Order By: Relevance
“…Using data from 23 OECD countries, Benz and Frey (2008) showed that the self-employed are signi…cantly more satis…ed with their jobs than employed individuals, and documented that such higher job satisfaction is attributable mainly to the more interesting jobs and greater autonomy that self-employment entails. Along similar lines, Chirkov et al (2003) showed that, across diverse cultures and social practices, autonomy is associated with well-being.…”
Section: Introductionmentioning
confidence: 83%
“…Using data from 23 OECD countries, Benz and Frey (2008) showed that the self-employed are signi…cantly more satis…ed with their jobs than employed individuals, and documented that such higher job satisfaction is attributable mainly to the more interesting jobs and greater autonomy that self-employment entails. Along similar lines, Chirkov et al (2003) showed that, across diverse cultures and social practices, autonomy is associated with well-being.…”
Section: Introductionmentioning
confidence: 83%
“…values of the culture into which they are primarily socialized (Chirkov, Ryan, Kim, & Kaplan, 2003). This cultural internalization process is complicated for immigrants, who must find ways to internalize the guidelines of secondary, and even tertiary, cultural identities and simultaneously find ways to integrate these sometimes seemingly disparate identities (Downie, Koestner, ElGeledi, & Cree, 2004).…”
mentioning
confidence: 99%
“…Other socioeconomic factors such as experience, gender and income should also be investigated. Another important limitation may be the effect of organization and culture, since the studies of Calhoun, Teng & Cheon [54], Chirkov, Ryan & Kim [55] and other researchers demonstrated that culture and organizational structure affects use of ICT in significant ways. Alternatively, Viberg & Grönlund [56] indicated that technology itself is more important than culture and other demographic factors.…”
Section: Resultsmentioning
confidence: 99%